2020
DOI: 10.1039/d0ma00139b
|View full text |Cite
|
Sign up to set email alerts
|

Development of fluorescent sensors based on a combination of PET (photo-induced electron transfer) and FRET (Förster resonance energy transfer) for detection of water

Abstract: Fluorescent sensors DJ-1 and DJ-2 with a large Stokes shift (SS) based on a combination of photo-induced electron transfer (PET) and Förster resonance energy transfer (FRET) for the detection of water in solvents have been developed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 48 publications
0
17
0
Order By: Relevance
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14] Consequently, fluorescent sensors for water are one of the most promising functional materials contributing to the achievement of the 2030 agenda for Sustainable Development Goals (SDGs), which has been adopted by all United Nations Member States in 2015 and provides a shared blueprint for peace and prosperity for people and the planet now and in the future. Actually, some kinds of organic fluorescent sensors and polymers for the determination of water content based on ICT (intramolecular charge transfer), [15][16][17][18][19][20][21][22][23][24] ESIPT (excited state intramolecular proton transfer), [25][26][27][28] PET (photo-induced electron transfer), [29][30][31][32][33][34][35][36] or solvatochromism [37][38][39][40][41][42] have been designed and synthesized. The optical sensing properties of these fluorescent sensors for the detection and quantification of water content were investigated from the viewpoints of the relationship between ICT, ESIPT, PET, or solvatochromic characteristics and the intermolecular ...…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14] Consequently, fluorescent sensors for water are one of the most promising functional materials contributing to the achievement of the 2030 agenda for Sustainable Development Goals (SDGs), which has been adopted by all United Nations Member States in 2015 and provides a shared blueprint for peace and prosperity for people and the planet now and in the future. Actually, some kinds of organic fluorescent sensors and polymers for the determination of water content based on ICT (intramolecular charge transfer), [15][16][17][18][19][20][21][22][23][24] ESIPT (excited state intramolecular proton transfer), [25][26][27][28] PET (photo-induced electron transfer), [29][30][31][32][33][34][35][36] or solvatochromism [37][38][39][40][41][42] have been designed and synthesized. The optical sensing properties of these fluorescent sensors for the detection and quantification of water content were investigated from the viewpoints of the relationship between ICT, ESIPT, PET, or solvatochromic characteristics and the intermolecular ...…”
Section: Introductionmentioning
confidence: 99%
“…OF-1 and OF-2 have a methoxy group as an electron-donating substituent and a cyano group as an electronwithdrawing substituent, respectively, at the para position on PhenylBPin. [29][30][31][32][33][34][35][36] In each sensor, the PET takes place from the nitrogen atom of the amino moiety to the photoexcited fluorophore (anthracene) skeleton in the absence of water, leading to fluorescence quenching. The addition of water to organic solvents containing the PET-type fluorescent sensors causes a drastic and linear enhancement of fluorescence emission as a function of water content, which is attributed to the suppression of PET; that is, the nitrogen atom of the amino moiety is protonated or strongly interacts with water molecules, leading to the formation of the PET inactive (fluorescent) species such as OM-1a, OF-1a, or OF-2a.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, concern has been raised about the development of uorescent sensors and their functional materials such as polymer lms and sensor-immobilized membranes for visualizing water in solutions, solids, and gas or on material surfaces, from the viewpoint of their potential applications to environmental and quality control monitoring systems and industry, as well as fundamental study in photochemistry, analytical chemistry, and photophysics. Several investigations have been conducted on the design and synthesis of organic uorescent sensors and polymers for the detection of water based on ICT (intramolecular charge transfer), [24][25][26][27][28][29][30][31][32][33][34] ESIPT (excited state intramolecular proton transfer), [35][36][37][38] PET (photo-induced electron transfer), [39][40][41][42][43][44][45][46] or solvatochromism [47][48][49][50][51][52] and the elucidation of the optical sensing properties based on changes in wavelength, intensity, and lifetime of uorescence emission depending on the water content. It was demonstrated that most of ICT-and ESIP-type uorescent sensors and uorescent conjugated polymers exhibited attenuation of the uorescence emission, that is, uorescence quenching (turn-off) systems with the increase in water content in solvents, and were suitable for the detection and quantication of a trace amount of water (below 1-10 wt% in almost every case) in solvents.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11] Moreover, fluorescent sensors for water have the potential to be functional materials, which would allow the visualization as well as detection and quantification of moisture or water droplets on material surfaces, and have promise to be applied to environmental, biomedical, and quality control monitoring systems. [12][13][14][15][16][17][18] Indeed, various kinds of organic fluorescent sensors for the determination of the water content in solvents based on their intramolecular charge transfer (ICT), [19][20][21][22][23][24][25][26][27][28][29] excited state intramolecular proton transfer (ESIPT), [30][31][32][33] photoinduced electron transfer (PET) [34][35][36][37][38][39][40][41] or solvatofluorochromic properties [42][43][44][45][46]…”
Section: Introductionmentioning
confidence: 99%